2021
DOI: 10.1002/jmri.27639
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial T1 Values at 1.5 T: Normal Values for General Electric Scanners and Sex‐Related Differences

Abstract: Background No data are available about normal ranges for native T1 in human myocardium using General Electric (GE) scanners. Purpose To establish normal ranges for myocardial T1 values and evaluate regional variability and the influence of physiological factors. Study type Prospective. Subjects One hundred healthy volunteers with normal electrocardiogram, no cardiovascular/systemic diseases, or risk factors (age range: 20–70 years; 50 females). Field Strength/Sequence 1.5 T/Steady‐state free precession cine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Meta-regression analysis showed that heterogeneity in native T1 values among AFD patients could be explained by two major variables, gender and LVH. The cause of higher myocardial native T1 values in pre-menopausal women is not completely defined and it relies on different factors, at least in part explained by thinner myocardial walls with a predisposition to partial-volume effect, lower hematocrit values, and different myocardial characteristics due to the hormone status [ 33 ]. In addition, AFD genetic inheritance is recessive X-linked and therefore in hemizygous men, enzyme α-galactosidase A activity is completely absent, while in heterozygous women it is guaranteed by the presence of wild-type gene on the other allele [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-regression analysis showed that heterogeneity in native T1 values among AFD patients could be explained by two major variables, gender and LVH. The cause of higher myocardial native T1 values in pre-menopausal women is not completely defined and it relies on different factors, at least in part explained by thinner myocardial walls with a predisposition to partial-volume effect, lower hematocrit values, and different myocardial characteristics due to the hormone status [ 33 ]. In addition, AFD genetic inheritance is recessive X-linked and therefore in hemizygous men, enzyme α-galactosidase A activity is completely absent, while in heterozygous women it is guaranteed by the presence of wild-type gene on the other allele [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the administration of the contrast agent, a sequence MOLLI SSFP for native T1 mapping was performed. Native T1 values were calculated by dedicated postprocessing software (Circle Cardiovascular Imaging, Alberta, Canada) and significantly shortened than normal values of the Laboratory were obtained (global T1 of LV was 885 ms, normal value ≥ 928 ms) ( Figure 3 ) ( 16 ). No areas of LGE (defined as hyperintense areas after administration of gadoteric acid ≥ 6 standard deviations than a region of interest in the background) were detected in the myocardium, covering the entire left ventricle from the mitral valve plane to the apex ( Figure 4 ).…”
Section: Case Descriptionmentioning
confidence: 99%
“…In this JMRI issue, the work by Meloni et al contributes to this body of knowledge by providing native T1 myocardium values for the GE 1.5 T scanner platform. 4 A more important contribution of Meloni et al's work is the assessment of physiological variation of native T1 values. They comprehensively investigated the segmental variation, gender-based variation, and cardiac phase-based variation in native myocardial T1 values.…”
mentioning
confidence: 99%
“…Acknowledging the different sources of variability, imaging sites are encouraged to measure their site‐specific native T1 reference values using the sequence, scanner platform, postprocessing tools, and population for their intended clinical use. In this JMRI issue, the work by Meloni et al contributes to this body of knowledge by providing native T1 myocardium values for the GE 1.5 T scanner platform 4 …”
mentioning
confidence: 99%